FRI0402 Vascular changes in choroid plexus in patients with raynaud's phenomenon suspected secondary to a connective tissue disease. (23rd January 2014) - Ingegnoli, F.; Gualtierotti, R.; Miserocchi, E.; Modorati, G.; Del Turco, C.; Gagliardi, M.; Parrinello, G.; Schioppo, T.; Zeni, S.; Meroni, P. L.; Pierro, L.
Abstract : Background: The early identification of Raynaud's phenomenon (RP) suspected secondary to a connective tissue disease (CTD) is fundamental to treat promptly the related organ manifestations. Among the potential clinical complications, eye involvement is often overlooked, even if it is known that systemic vascular dysregulation is able to induce vasospasm in the retinal vessels and retinal blood flow abnormalities. Objectives: To evaluate the presence of vascular eye involvement measuring the choroidal and macular thickness in a cross-sectional cohort of RP suspected secondary to a CTD. Methods: Consecutive RP suspected secondary to a CTD were enrolled. Inclusion criteria were: 1) RP; 2) nosymptoms/signs suggesting a CTD; 3) major capillary abnormalities at nailfold capillaroscopy and/or positive anti-nuclear antibodies (ANA) by IFF and blotting; 4) no visual symptoms. Patients underwent a complete ocular examination including: best corrected visual acuity, slit lamp biomicroscopy, intraocular pressure measurements and fundus examination. Choroidal thickness (CT) was assessed using the Zeiss Cirrus Spectral Domain Optical Coherence Tomography (SD-OCT) with enhanced depth imaging (EDI) scan system at the fovea and up to 1 mm at intervals of 2 mm from the fovea in the superior, inferior, nasal and temporal choroid; central fovea thickness (CFT) was also measured. 26 healthy, sex and aged-matched, subjects were analysed as control group. Statistical analysis was performed by Mann-Whitney test. Results: 20 subjects were included in the study (mean age 51.85 years, 18 females), 75% (15 out of 20) had positive ANA test, of whom 11 (55%) with anti-centromere pattern. 13 out of 20 (65%) showed scleroderma pattern at nailfold capillaroscopy. Slit lamp biomicrocopy was within normal limits in all patients and fundus examination revealed normal arterial and venous vessels with no capillary abnormalities. The mean best corrected visual acuity was 20/40 and the mean intraocular pressure measurement was 14 mmHg. Choroidal thickness measurements were significantly thinner than healthy control in the subfoveal region (mean 256.82 µm vs 313.22 µm; p=0.0031). Similar results were observed in the superior, temporal and nasal sectors of the retina at 1 and 2 mm from the fovea: inner superior (mean 250.48 vs 293.22; p=0.0014), outer superior (mean 241.77 vs 293.3; p= 0.016); inner nasal (mean 231.97 vs 297.44; p= 0.0003), outer nasal (mean 185.12 vs 289; p= 0.0001); inner temporal (mean 262.91 vs 313.22; p=0.0031), outer temporal (mean 241.21 vs 282.56; p= 0.045). Choroidal thickness was overall thinned in the inferior sectors: inner inferior (mean 258.29 vs 293.15; p= 0.0003), outer inferior (mean 252.29 vs 289.89; p= 0.067). CFT was also thinner in RP suspected secondary to a CTD than in healthy controls (mean 257.44 vs 275.18; p=0.0061). Conclusions: Thinner choroidal thickness was observed in RP suspected secondary to a CTD without evident visual symptoms. This suggests a compromisedchoroidal perfusion, and the presence of an early involvement of ocular microcirculation since the very early phase of a scleroderma spectrum disease. Disclosure of Interest: None Declared